Links Between Air Quality and Economic Growth - Shanthi Nataraj, Ramya Chari, Amy Richardson, and Henry H. Willis (RAND Corporation, 2013)
This report presents the results of a RAND Corporation study for the Heinz Endowments. The study sought to better characterize the links between air quality and economic development to help understand how improving air quality in the Pittsburgh region could affect local economic growth. The findings presented here are based on a review of the existing, national studies on links between air quality and economic growth and on an extrapolation of some of those results to the Pittsburgh region; the findings were also informed by discussions with individuals engaged in economic development and air pollution policy from the private, public, and nonprofit sectors. The findings should be of interest to local policymakers, individuals, and organizations working in the areas of economic development and environmental policy.